PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE PEMECAHAN MASALAH - Andi Muhammad Ajiegoena (TARBIYA: Journal of Education in Muslim Society, 2014)
Abstract: The objective of this research is to know learning process to increase elementary student learning outcomes in math study through problem solving method. The research also to find out the changing of learning outcomes after acting method. About twenty one students of SDN 22 Belopa the subject of this research. The research uses action research method by Kemmis and Mc. Taggart which consist of four steps: (a) planning, (b) action, (c) observation, and (d) reflection. The data collecting techniques use field notes, documentations, and observation. This research also uses quantitative and qualitative analyses. The result of the research indicate that learning outcomes of math were improvements with using problem solving method after acting in learnig. The significant improvement was proved with the test of relsulting student from 66.6 % at the first cycle, and raising level 80.9% the second cycle. DOI: 10.15408/tjems.v1i1.1116